HUBUNGAN KELIMPAHAN FITOPLANKTON, KONSENTRASI KLOROFIL-a DAN KUALITAS PERAIRAN PESISIR SUNGSANG, SUMATERA SELATAN - Ridho, Moh. Rasyid; Patriono, Enggar; Mulyani, Yenni Sri (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2020)
Diversity and abundance of fish are rely on fitoplankton abundance as food, meanwhile abundance of phytoplankton is depend on waters quality. In order to understand relationship among those component, this study was carried out to analyzed correlation among phytoplankton abundance chlorophyll-a concentration and water quality. This study was conducted in the coastal waters of sungsang, Banyuasin Regency from July until August 2017. Sample collected using purposive sampling method. Results of the research showed that clarity around 6.3-45.5%, turbidity 2-4 NTU, temperature 29.6-30.8oC, pH 6.0-7.7, salinity 0-16 ppt, DO 5.33-6.50 mg/L, BOD 0.4-3.6 mg/L, ammonia 0.1-0.32 mg/L, phosphate 0.01-2.16 mg/L, nitrate 0.06-2.96 mg/L, chlorophyll-a 1,68-20,6 mg/m3. There was positive correlation among chlorophyll-a and phytoplankton, phosphate, nitrate, DO, BOD5 about 95.5%, 91%, 76.6%, 82.2%, -63%, respectively. The higher the concentration of phosphate and nitrate the higher the concentration of chlorophyll-a, and the higher the concentration of chlorophyll-a causes the higher the concentration of dissolved oxygen. The higher the BOD5 and ammonia, the lower the concentration of chlorophyll-a.